PEMAKNAAN PESAN KOMUNIKASI PUBLIK DALAM DEBAT CALON PRESIDEN 2019 - Mutiara, Ni Luh Arisma; Natalia, El Chris (School of Communication - Atma Jaya Catholic University of Indonesia, 2019)
Public communication is the process of using messages to generalize meaning in situations where one source spreads the message to the recipient and the recipient provides feedback with questions and answers and nonverbal communication. The purpose of this study is to analyze the meaning of the public presidential communication messages related to the environment in the second video debate 17 February 2019. This study used a qualitative approach with Roland Barthes semiotic method. The study was conducted by examining video documents and analysis by combining Public Communication Theory, Environmental Communication, and Barthes Semiotic studies in finding meanings. The results showed the meaning of the message of the presidential debate was based on the essence of culture and its relationship with the media, public, policy on environmental issues.